Organizational Behavior - Luthans, Fred (New York McGraw-Hill Irwin, 2002)
Dealing with the area of organizational behaviour, this text is aimed at professors who take a research based and conceptual approach to their OB course.
Include Index
Keywords: Organizational behavior -- Management -- Organization -- Psychology, Industrial